2016
DOI: 10.1001/jamaoncol.2016.1197
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Pazopanib Therapy Prior to Planned Nephrectomy in Metastatic Clear Cell Renal Cancer

Abstract: Importance: The role of cytoreductive nephrectomy in patients with metastatic renal cancer in the era of targeted therapy is uncertain. Data on targeted therapy prior to nephrectomy is lacking.Objective: To establish the safety and efficacy of upfront pazopanib prior to cytoreductive nephrectomy in previously untreated metastatic clear cell renal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 17 publications
5
38
1
3
Order By: Relevance
“…Powles and colleagues reported the outcomes of a single arm phase II study of a 102 patients with mRCC treated with pazopanib for 12-14 weeks [Powles et al 2013]. A total of 81% had SD, with 14% achieving PR.…”
Section: Tumor Downsizingmentioning
confidence: 99%
“…Powles and colleagues reported the outcomes of a single arm phase II study of a 102 patients with mRCC treated with pazopanib for 12-14 weeks [Powles et al 2013]. A total of 81% had SD, with 14% achieving PR.…”
Section: Tumor Downsizingmentioning
confidence: 99%
“…It was recently reported that the expression of programed cell death-ligand 1 (PD-L1) in the immune component increased with pazopanib therapy, while CD8 expression decreased (4). It is unclear if the same happens with sunitinib (5, 6), but it may be an explanation to justify the response achieved in our case and in the case report by Geynisman.…”
Section: Background and Discussionmentioning
confidence: 99%
“…The results of single-agent phase 2 clinical trials with neoadjuvant anti-angiogenic agents (e.g., vascular endothelial growth factor receptor tyrosine kinase inhibitors [VEGFr TKI], VEGF antibodies, mammalian target of rapamycin [mTOR] inhibitors) demonstrate feasibility but not remarkable down-staging, and results with newer agents (i.e., immuno-oncology agents) will not be available in the near future. [9][10][11][12] Some patients deemed medically or surgically inoperable at diagnosis may have a dramatic radiological and/or clinical response to systemic therapy. A multidisciplinary team should re-evaluate them if there is any question that they may have converted to an operable state.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%